1998
DOI: 10.1161/01.res.82.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Inhibits Lipopolysaccharide-Induced Cardiac Expression of Tumor Necrosis Factor-α

Abstract: —Tumor necrosis factor-α (TNF-α) is elevated in the failing heart. Very little is known about regulation of TNF-α in cardiomyocytes. TNF-α expression by macrophages is diminished by adenosine. Therefore, we hypothesized that a similar mechanism might occur in the heart. Neonatal rat myocytes were stimulated with lipopolysaccharide (LPS), and TNF-α was measured by ELISA. In the absence of LPS, myocytes did not release TNF-α in the medium. After exposure to LPS, TNF-α increased to 70.1±3.5 pg/mL at 6 hours. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 42 publications
6
62
0
Order By: Relevance
“…Also, the NO donor SNAP did not induce contractile dysfunction in the absence of coronary microembolization. Finally, given the otherwise established anti-inflammatory properties of endogenous NO, 43,44 our data are consistent with the idea that the suppression of basal and/or stimulated eNOS-derived NO acts to remove a restraining influence on adenosine release, 45 and the increased adenosine levels may then suppress TNF-␣, 46,47 sphingosine, and, finally, contractile dysfunction. Indeed, an involvement of adenosine is suggested by the tendency of regional myocardial blood flow to increase over time in the L-NAME group.…”
Section: Thielmann Et Al Signal Transduction In Coronary Microembolizsupporting
confidence: 86%
“…Also, the NO donor SNAP did not induce contractile dysfunction in the absence of coronary microembolization. Finally, given the otherwise established anti-inflammatory properties of endogenous NO, 43,44 our data are consistent with the idea that the suppression of basal and/or stimulated eNOS-derived NO acts to remove a restraining influence on adenosine release, 45 and the increased adenosine levels may then suppress TNF-␣, 46,47 sphingosine, and, finally, contractile dysfunction. Indeed, an involvement of adenosine is suggested by the tendency of regional myocardial blood flow to increase over time in the L-NAME group.…”
Section: Thielmann Et Al Signal Transduction In Coronary Microembolizsupporting
confidence: 86%
“…29 Adenosine is known to inhibit norepinephrine release from presynaptic vesicles, 27 reduce the production of ET-1, 28 and reduce tumor necrosis factor-␣ production. 20 Recently, we also found that, whereas 8-sulfophenyltheophylline significantly increased myocardial oxygen consumption in dogs with failing hearts, it had no effect on oxygen consumption in normal dogs, 26 suggesting that endogenous adenosine may help reduce myocardial oxygen demand, particularly in the failing heart. Studies in rats in which extracellular adenosine was increased by blockade of adenosine uptake with dipyridamole 7 also reported attenuation of pressure-overloadinduced myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 96%
“…Because in vivo adenosine can increase blood flow, 26 reduce inflammatory responses, 20 inhibit norepinephrine release from nerve endings, 27 and decrease ET-1 production, 28 it was important to determine whether the amplified mTOR/p70S6 signaling in the KO mice was the result of indirect effects of adenosine that caused paracrine regulation of these signaling pathways or a direct effect of adenosine on cardiomyocytes. Therefore, we examined the effect of the adenosine analogue CADO on phenylephrine (PE)-induced hypertrophy and ac- , and mTOR ser2448 in heart lysates, as measured by Western blot and scanning densitometry.…”
Section: Adenosine or Adenosine Analogue Attenuates Cardiac Myocyte Hmentioning
confidence: 99%
“…Several of these effects could be explained by the ability of adenosine to suppress TNF produced by activated macrophages and Kupffer cells (Bouma et al, 1994;Reinstein et al, 1994;McWhinney et al, 1996;Bowlin et al, 1997;Hasko et al, 2000a) and to suppress expression of adhesion molecules by activated human endothelial cells (Bouma et al, 1996). Indeed, suppression of lipopolysaccharide (LPS)-induced TNF production by adenosine has been demonstrated in human cardiac tissue (Wagner et al, 1998a, b). Additionally, adenosine has also been shown to modulate the signaling of inflammatory cytokines, including TNF (de la Harpe and Nathan, 1989;Sullivan et al, 1990;Bergmann et al, 1994;Liu et al, 2000) and interleukin-1 (IL-1) (Pahl 1999;John et al, 2001).…”
Section: Introductionmentioning
confidence: 99%